JUSTIFICATION OF THE PARAMETERS AND DEVELOPMENT OF THE DESIGN OF THE MECHANISM OF AUTOMATED SELECTION AND SUPPLY OF CUTTINGS IN ENERGY CULTURE PLANTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
An important field of bioenergy development is the use of biomass energy, which requires significant amounts of raw materials grown in the fields. One of the prospective sources of such raw materials is the planting of fast-growing wood species capable of restoring the above-ground part after cutting in a short period of time. The article sets out the task of developing approaches and constructive solutions regarding the possibilities of creating highly productiveaggregates for planting such woody energy crops as willow, poplar, and others that are propagated by cuttings. The analysis of the current state of development of this issue revealed that one of the factors inhibiting the process is the insufficient level of developments and their implementation in the field of automation of the technological process of planting. In most technical solutions, the use of the labor of the planter is included, which makes the process as a whole dependent on human capabilities and other related factors.The work is intended to solve the empirical task of developing an automated planter for plants planted with lignified cuttings.To develop an automated system that would provide uninterrupted and uniform supply of cuttings to the coulter of the planter, a two-factor experiment was conducted on a developed laboratory stand simulating a slotted hopper. As a result of research, it was found that the optimal width of the unloading window of the feeder should be at least 80 mm, and the optimal angles of inclination of the slotted hopper walls should be at least 40°. These parameters will provide complete and continuous unloading of cuttings both in the absence of external forces acting on them (oscillations, vibrations, etc.) and with them. Taking into account the analysis of existing technical solutions and the results of a laboratory experiment, a number of solutions were synthesized, which were used in the development of a new construction of the cuttings unloading mechanism. The developed construction of the mechanism of automated dosing, selection and supply of cuttings for the planter of energy willow is protected by a patent and embodied in a single-row design and tested in field conditions. Such a planting machine allows to plant without the support of a planter, whose functions are reduced to periodically loading the slotted hopper with cuttings previously oriented in one direction.